Penerapan Discharge Planning terhadap Kepuasan Pasien pada Asuhan Keperawatan - Yati Sumiati; Tri Kurniati; Luknis Sabri; Muhammad Hadi; Tini Suminarti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine discharge planning on patient satisfaction when the patient is treated at the Jakarta Hajj Hospital. This research method is using quantitative research with a cross-sectional design. The results of the study obtained an overview of the influence of the implementation of discharge planning on the most dominant satisfaction in nursing care at the Jakarta Hajj Hospital, which had the most effect on reliability satisfaction (reliability) p-value = 0.002 (Î± <0.05). In conclusion, discharge planning affects satisfaction during treatment; the dominant indicator of reliability is discharge planning. Keywords: Discharge Planning, Satisfaction